Brazil 18: a visão de cinco brasileiros residentes ao estado da Califórnia acerca da eleição de Bolsonaro - Abdalla, Samir Bueno [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
This audiovisual piece is intended to illustrate, with examples, the view that the Brazilian resident outside the country had, and has, about the election of Jair Messias Bolsonaro, more precisely in the state of California, on the west coast of the United States of America. Produced during the last term of the graduation degree in Social Communication with emphasis on journalism, this piece aim is to be a simple, direct and fair source of information on a subject that is not very approached in the discussion

Essa peça audiovisual tem como intuito ilustrar, com exemplos, a visão que o brasileiro residente fora do país teve e tem acerca da eleição de Jair Messias Bolsonaro, mais precisamente no estado da Califórnia, na costa oeste dos Estados Unidos da América. Produzido durante o último semestre do curso de graduação em Comunicação Social com ênfase em jornalismo, a peça busca ser fonte simples, direta e justa de informação sobre um assunto pouco abordado na discussão
Keywords: Brasileiros - Estados Unidos; Eleições - Brasil; Brazilians - United States; Califórnia (Estados Unidos)